1996
DOI: 10.1074/jbc.271.9.5025
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Novel Stress Protein, the 150-kDa Oxygen-regulated Protein (ORP150), from Cultured Rat Astrocytes and Its Expression in Ischemic Mouse Brain

Abstract: As the most abundant cell type in the central nervous system, astrocytes are positioned to nurture and sustain neurons, especially in response to cellular stresses, which occur in ischemic cerebrovascular disease. In a previous study (Hori, O., Matsumoto, M., Kuwabara, K., Maeda, M., Ueda, H., Ohtsuki, T., Kinoshita, T., Ogawa, S., Kamada, T., and Stern, D. (1996) J. Neurochem., in press), we identified five polypeptide bands on SDS-polyacrylamide gel electrophoresis, corresponding to molecular masses of about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…We observed detectable levels of this protein only in the presence of L-DOPA regardless of the oxidative stress conditions (Table 2) suggesting that L-DOPA may aid hypoxia condition in cells. It has been shown in rat astrocytes that ORP150 is induced by hypoxia within 24 hours, augmented further during early re-oxygenation, and thereafter decreasing to baseline levels by 24 hours in normoxia [49]. Furthermore, the hypoxia-mediated induction of ORP150 appears specific as stress conditions such as heat shock, H 2 O 2 , cobalt chloride, 2-deoxyglucose, or tunicamycin does not affect ORP150 levels [49].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed detectable levels of this protein only in the presence of L-DOPA regardless of the oxidative stress conditions (Table 2) suggesting that L-DOPA may aid hypoxia condition in cells. It has been shown in rat astrocytes that ORP150 is induced by hypoxia within 24 hours, augmented further during early re-oxygenation, and thereafter decreasing to baseline levels by 24 hours in normoxia [49]. Furthermore, the hypoxia-mediated induction of ORP150 appears specific as stress conditions such as heat shock, H 2 O 2 , cobalt chloride, 2-deoxyglucose, or tunicamycin does not affect ORP150 levels [49].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown in rat astrocytes that ORP150 is induced by hypoxia within 24 hours, augmented further during early re-oxygenation, and thereafter decreasing to baseline levels by 24 hours in normoxia [49]. Furthermore, the hypoxia-mediated induction of ORP150 appears specific as stress conditions such as heat shock, H 2 O 2 , cobalt chloride, 2-deoxyglucose, or tunicamycin does not affect ORP150 levels [49]. Interestingly, exposure to dopamine has similar ORP induction effects as hypoxia in PC12 cells [50].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, HYOU1 is upregulated in some human cancers, including head and neck and breast cancers (34,35). The HYOU1 transcript was originally cloned from astrocytes under hypoxic conditions (36), which makes it a protein relevant to KSHV biology, since hypoxia plays a role in the KSHV life cycle (37). Previous work has indicated that HYOU1 can suppress hypoxia-induced cell death (38) and induce angiogenesis by facilitating VEGF processing (39).…”
mentioning
confidence: 99%
“…GRP170, encoded in humans by HYOU1, is a large HSP70/HSP110-like protein in the ER 184 that is induced by hypoxia 185,186 (see figure).…”
Section: Figurementioning
confidence: 99%